Nghiên cứu tương tác của Axit humic với một số cation kim loại bằng các phương pháp cực phổ - Huệ, Nguyễn Đức; Luyến, Nguyễn Việt; Nghi, Tử Vong; Đán, Phạm Ngọc; Hùng, Đào Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 1 No 3, 1985)
Abstract